2001
DOI: 10.1023/a:1012222522359
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Human low-grade gliomas represent a population of brain tumors that remain a therapeutic challenge. Preclinical evaluation of agents, to test their preventive or therapeutic efficacy in these tumors, requires the use of animal models. Spontaneous gliomas develop in models of chemically induced carcinogenesis, such as in the transplacental N-ethyl-N-nitrosourea (ENU) rat model. However, without the ability to detect initial tumor formation, multiplicity or to measure growth rates, it is difficult to test compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To test our strategy to block SDF-1 interaction with both its receptors CXCR4 and CXCR7, we used N -ethyl- N -nitrosourea (ENU)–induced brain tumors in the Sprague-Dawley rat, a model that has proved to be extremely resistant to anticancer therapy in prior studies by a variety of investigators 17,18 (L. Recht, unpublished). After in utero exposure to ENU on days 17–18 of gestation, the pups appeared healthy for over 100 days, at which time they began to demonstrate neurological distress and die progressively from brain tumors from day 120 after birth.…”
mentioning
confidence: 99%
“…To test our strategy to block SDF-1 interaction with both its receptors CXCR4 and CXCR7, we used N -ethyl- N -nitrosourea (ENU)–induced brain tumors in the Sprague-Dawley rat, a model that has proved to be extremely resistant to anticancer therapy in prior studies by a variety of investigators 17,18 (L. Recht, unpublished). After in utero exposure to ENU on days 17–18 of gestation, the pups appeared healthy for over 100 days, at which time they began to demonstrate neurological distress and die progressively from brain tumors from day 120 after birth.…”
mentioning
confidence: 99%
“…To test NOX-A12 in vivo, the authors used N-ethyl-N-nitrosourea (ENU)-induced brain tumors in the Sprague-Dawley rat, a model that has been proven to be extremely resistant to anticancer therapy [110]. The authors demonstrated that NOX-A12-mediated SDF-1 blockade was indeed effective in inhibiting or delaying GBM recurrences following irradiation in this model.…”
Section: Nox-a12 Aptamermentioning
confidence: 99%
“…In order to follow the angiogenesis process during the neoplasia genesis, we have used an endogenous glioma model. It was generated by transplacental administration of ethylnitrosourea (ENU) in rats [28, 66, 67]. …”
Section: An Experimental Model Of Endogenous Gliomamentioning
confidence: 99%